Operation analysis and parameter optimization of drum type soil-covering device - Xu, Hongzhen; Tian, Dongyang; Liu, Jiaodi; Niu, Zhenhua; Li, Qiang (International Journal of Agricultural and Biological Engineering, 2021)
Up-film pot seedling transplanter is not stable in soil output, causing exposed and fallen seedlings, insufficient up-film daylighting and other problems. Based on the research on soil-covering process and principle of soil-covering device of transplanter, a theoretical model of the soil taking volume was established, the soil output principle of soil-covering drum was analyzed, the theoretical soil output volume was calculated, and the influences of structural parameters on soil output were studied. The field tests based on the influences of structural parameters on soil output was conducted using Box-Behnken experiment design, and a mathematical model between soil output and declination, vertical center distance (i.e. the depth in soil of soil-covering disc), and height of screw blades of soil-covering disc was established. Optimized analysis on the response surface was conducted based on parameter range and target soil output range. Results show that the soil output increases when the declination of the soil-covering disc increases from 20° to 40°, or the vertical center distance increases from 4-6 cm; the change of screw blade height has small impact on the soil output; The optimal structural parameters combination for the soil-covering device was obtained with the included angle of soil-covering disc of 37°, vertical center distance of 5.5 cm, and height of screw blades of 5cm. With this optimal parameters combination, the soil output of 1 m soil-cover belt is 4.84 kg, which is basically the same with the actual volume of 4.53 kg and can ensure the stability of the soil output and provide reference for the optimization design of soil-covering device.Keywords: up-film transplanting soil-covering, soil-covering device, soil output, model, optimizationDOI: 10.25165/j.ijabe.20211403.5383Citation: Xu H Z, Tian D Y, Liu J D, Niu Z H, Li Q. Operation analysis and parameter optimization of drum type soil-covering device. Int J Agric & Biol Eng, 2021; 14(3): 123–129.